Non-union Treatment Outcomes in South-East Nigeria - Madu, Kenechi Anthony; Nnyagu, Henry; Ede, Osita (Nigerian Journal of Orthopaedics and Trauma, 2018)
Introduction: Management of non union of long bones can be challenging and frustrating for the orthopaedic surgeon. In sub Saharan Africa, the bulk of surgeries done by the orthopaedic surgeon may include a significant number of non union of long bones. This is largely because of the strong affinity for seeking treatment from the traditional bone setter as the first on call following fractures in most cases. The orthopaedic surgeon frequently gets to manage the complications arising from such treatment. In managing such cases, adjunctive therapies targeted at increasing union rates which are available to surgeons elsewhere are frequently lacking. Methodology: The study was aimed at determining the outcome of surgeries done for non union of long bones in our institution. It was a retrospective study spanning a 3 year period, from April 2013 to March 2016, involving 80 patients who presented with non union of any of the 3 long bones which had not previously been surgically managed. The patients had surgery with plate / screw construct or a solid intramedullary nail. Outcome measures analysed included occurrence of union, time to union and occurrence of complications with each treatment method for the 3 long bones. Results: We recorded a union rate of 79.2% for all 3 long bones. Majority of the femoral non unions were nailed while the humerus was more commonly plated. The humerus did better with plating than it did when nailed, though nailed non unions were observed to unite faster. Femoral non unions united better when nailed than when plated, though the difference was not statistically significant. Complications rates were higher following plating for femoral non unions. Complications following humeral non union plating were also higher than observed for nailing, with radial nerve palsy occurring in 23.5% of platings. Tibial non unions demonstrated high union rates irrespective of treatment method used. Conclusion: In conclusion, management of non union of long bones is still a challenge with a recurrence rate of 10.8%. Humeral non unions do better when plated as opposed to the femur. Tibial non unions do well with either plating or nailing.